Crouzon syndrome is not linked to craniosynostosis loci at 7p and 5qter. Issue 3 (March 1994) - Reardon, W; van Herwerden, L; Rose, C; Jones, B; Malcolm, S; Winter, R M
Abstract : Evidence for linkage has been sought, in four pedigrees with Crouzon syndrome, between polymorphic markers known to be linked to the Saethre-Chotzen locus on 7p and another form of autosomal dominant craniosynostosis on 5q. The data we present exclude Crouzon syndrome as an allelic variant at either of these known craniosynostosis loci.